HUBUNGAN SIKAP PERAWAT DENGAN STRES AKIBAT HOSPITALISASI PADA ANAK USIA PRA SEKOLAH DI RSU PANCARAN KASIH GMIM MANADO - Hulinggi, Ismanto; Masi, Gresty; Ismanto, Amatus Yudi (JURNAL KEPERAWATAN, 2018)
Abstract: Hospitalization in children is a stressful experience for both the children themselvesand their parents. The number of stressors experienced by children when undergoinghospitalization interfere adversely affecting the child's development. The hospital environmentcanbe a cause of stress and anxiety in children.In line with the increase in the number ofchildren who were hospitalized late population at risk of an increase in children who havedevelopmental disorders. The Purpose of this study was to is to analyze correlation betweennurse behavior and stres of hospitalzation to Children at Pre School at Pancaran KasihChristian Evangelical Church In Minahasa Hospital Manado. Methode in this study useddescriptive analytic with cross sectional design. Sampling technique using tipe judgementsampling involved 47 respondents. Results of this study based on chi-square the views of thefisherâ€™s exact test obtained Ï value=0,012. This means that the value of Ï is less than the valueof Î± (Î±=0.05), thus it can be said that H0 is rejected. Conclusion There is significantcorrelation between nurse behavior and stres of hospitalzation to Children at Pre School atPancaran Kasih Christian Evangelical Church In Minahasa Hospital Manado.Keywords : Between Nurse Behavior, Stres Of Hospitalzation, Children at Pre SchoolAbstrak: Hospitalisasi pada anak merupakan pengalaman yang penuh dengan stress, bagi anakitu sendiri maupun orang tua. Banyaknya stressor yang dialami anak ketika menjalanihospitalisasi menimbulkan dampak negatif yang menganggu perkembangan anak. Sejalandengan peningkatan jumlah anak yang dirawat dirumah sakit akhir-akhir ini, beresiko terjadipeningkatan populasi anak yang mengalami gangguan perkembangan. Tujuan penelitian iniadalah untuk menganalisis hubungan sikap perawat dengan stress akibat hospitalisasi pada anakusia pra sekolah di RSU Pancaran Kasih GMIM Manado. Metode penelitian yang digunakanyaitu deskriptif analitik dengan rancangan cross sectional. Teknik Pengambilan Sampel padapenelitian ini yaitu tipe judgement sampling dengan jumlah 47 sampel. Hasil Penelitianberdasarkan uji chi-square yang dilihat dari fisherâ€™s exact test diperoleh nilai Ï value=0,012.Hal ini berarti nilai Ï lebih kecil dari nilai Î± (Î±=0,05), dengan demikian dapat dikatakan bahwaH0 ditolak. Kesimpulan terdapat hubungan yang signifikan antara hubungan sikap perawatdengan stress akibat hospitalisasi pada anak usia pra sekolah di RSU Pancaran Kasih GMIMManado.Kata Kunci : Sikap Perawat, Stres Akibat Hospitalisasi, Anak Usia Pra Sekolah